Death Kongsi and the Survival of Chinese Death Processions in Padang City - Erniwati, Erniwati; Syafrina, Yelda; Febrianto, Adri; Susanti, Retnaningtyas (Universitas Negeri Padang, 2024)
This article explains how the ethnic Chinese of Padang maintain the continuity of the death procession in Chinese culture. This article uses a historical approach by utilizing sources in the form of Dutch period documents, organizational documents of Himpunan Tjinta Teman (HTT) and Himpunan Bersatu Teguh (HBT), newspaper news and literature studies on the death processions of ethnic Chinese in Indonesia and outside Indonesia, as well as observations and interviews with HBT and HTT funeral administrators. These sources are used to find facts related to the death processions carried out by ethnic Chinese and the existence of HBT and HTT as institutions organizing Padang Chinese funeral processions. Furthermore, the existing facts are analyzed using historical and ethnographic approaches. The findings of the article show that the ethnic Chinese of Padang still carry out and preserve the implementation of the Chinese cultural death procession in an organizational forum. In this case, the organization's function as the organizer of the death procession for Padang Chinese is the key to the survival and existence of the organization itself. Various Chinese cultures preserved and inherited in the HTT and HBT organizations, including the culture of death, are essential in forming self- and collective identity and solidarity of Chinese community groups in the city of Padang.